CONFORMAL ANOMALY IN ADS/CFT DUALITY AT D=4 - Ikhsan Arif, M
AdS/CFT correspondence is an example of gauge/gravity duality. This du- ality provides a link between quantum theory and gravity which is based on string theory. AdS/CFT makes it possible to analyze gauge theory on strong-coupling using AdS spacetime. This correspondence makes the as- sumption that the theory of gravity with negative cosmological constants or AdS space in dimensions 4+1 is equivalent to conformal eld theory at the boundary at a certain limit. The conformal anomaly is when the expected value of the energy-momentum tensor trace is not zero for a eld theory with conformal symmetry. This is due to the regularization and renormal- ization of the quantization procedure. In this paper, we will review the conformal anomalies in the four-dimensional conformal eld theory calcu- lated through the bulk/gravity theory in the ve-dimensional AdS asymp- totic space. AdS/CFT correspondence is obtained when calculated at the limit N to innity.